Análise da estrutura de governança dos arranjos produtivos locais do polo de confecção do norte-noroeste do estado do Paraná - Nagamatsu, Rosimeiri Naomi (2011)
This study aimed to examine the governance structures of identifying the logic of relations and the governance variables of the clothing sector APLs Polo Textile Clothing Paraná. To this end, we organized a theoretical framework that supported the changes in the course of history, the concepts of Productive Clusters and their main competitive advantages. Address the concepts and theoretical bases on Governance, which allowed us to understand the importance of its elements and structures allied to them. The methodological procedures adopted in this study were those relating to the case study. The procedures for data analysis were explanatory, descriptive and qualitative. We used primary data collected through semi-structured interviews and secondary data as well as direct observation of the researcher. The environmental analysis of the research focused on managers of APLs Governance Polo Textile Clothing Paraná. Data were analyzed by the inductive method, by analyzing the results obtained in the case study, comparing them with the theoretical aspects of this research. A main outcome was possible to know the main joint strategies employed by companies participating in the clusters of the Textile Clothing Polo Paraná. These strategies are developed by the thematic groups by means of a governance structure that aims to establish the actions that contribute to improving competitiveness.